Drug-excipient compatibility studies in binary mixtures of Avobenzone - Ceresole, Rita (2013)
During preformulation studies of cosmetic/pharmaceutical products, thermal analysis techniques are very useful to detect physical or chemical incompatibilities between the active and the excipients of interest that might interfere with safety and/or effi cacy of the fi nal product. Differential scanning calorimetry (DSC) was used as a screening technique for assessing the compatibility of avobenzone with some currently used cosmetic excipients. In the fi rst phase of the study, DSC was used as a tool to detect any interaction. Based on the DSC results alone, cetearyl alcohol, isopropyl myristate, propylparaben, diethylhexyl syringylidene malonate, caprylic capric triglyceride, butylated hydroxytoluene (BHT), glycerin, cetearyl alcohol/ceteareth 20, cetearyl alcohol/sodium lauryl sulfate/sodium cetearyl sulfate, and paraffi num liquidum exhibit interaction with avobenzone. Stressed binary mixtures (stored at 50°C for 15 days) of avobenzone and excipients were evaluated by high-performance liquid chromatography. Binary mixtures were further investigated by infrared (IR) spectroscopy. Based on DSC, isothermal stress testing, and fourier transform infrared results; avobenzone is incompatible with caprylic capric triglyceride, propylparaben, and BHT.